High-aluminum coal gangue active powder, preparation method and application thereof

CN122958089APending Publication Date: 2026-10-23CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510503748.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

煤矸石大量排放不仅占用土地、还会导致环境污染问题,如土壤污染、大气污染等,影响生态可持续发展

Benefits of technology

[0022]一、本发明使用高铝元素含量的煤矸石,其在煅烧活化粉碎后具有更多的非晶相成分,这些非晶相成分在参与到制备无机注浆加固材料组合物的水化反应中时,可以使材料的抗压强度和流动性能更优。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005369173290000071
    Figure BDA0005369173290000071
  • Figure BDA0005369173290000091
    Figure BDA0005369173290000091
Patent Text Reader

Abstract

The present application belongs to the field of coal gangue resource, and particularly relates to a high-aluminum coal gangue active powder and a preparation method thereof, which comprises the following steps: (S1) crushing coal gangue raw materials to obtain crushed materials; (S2) calcining the crushed materials to obtain calcined materials; (S3) grinding the calcined materials to obtain coal gangue powder; wherein the content of aluminum element in the coal gangue raw materials is greater than or equal to 30 wt%, and the content of amorphous phase is greater than or equal to 50%; the calcining temperature is 600-900 DEG C. The present application also relates to a composition of inorganic grouting reinforcement material, which comprises 2400-2550 parts by weight of coal gangue powder, 450-600 parts by weight of activator, 950-1000 parts by weight of water, 2-4 parts by weight of water reducing agent, 0.1-0.2 parts by weight of plastic expansion agent, 0.05-0.1 parts by weight of water retaining agent, and 0.5-1.5 parts by weight of defoaming agent. The coal gangue powder provided by the present application has high activity, and can partially replace cement in the preparation of the composition of inorganic grouting reinforcement material, thereby reducing the cement consumption, reducing carbon dioxide emission, and obtaining a composition with excellent fluidity, controllable setting time and excellent compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coal gangue resource utilization technology, specifically relating to a high-alumina coal gangue active powder, its preparation method, and its application. Background Technology

[0002] Coal gangue is a major solid waste discharged during coal mining and washing, accounting for approximately 15%-20% of total coal production. Currently, my country's cumulative coal gangue stockpiles exceed 5 billion tons, and this amount continues to increase with emissions. Large-scale coal gangue emissions not only occupy land but also cause environmental pollution problems such as soil and air pollution, impacting sustainable ecological development. The annual utilization rate of coal gangue is less than 60%, mainly used for mine backfilling and road paving. The low utilization rate is due to factors such as difficulties in implementing coal gangue utilization policies, outdated technology and facilities, and weak research foundations. Processing coal gangue into highly active powder can replace some cement clinker, reduce carbon emissions, and broaden the comprehensive utilization pathways of coal gangue.

[0003] Various activation methods, such as mechanical activation, thermal activation, chemical activation, and combined activation, are used to enhance the reactivity of coal gangue, enabling it to be used as an admixture to partially replace cement in the preparation of cementitious materials. Mechanical activation, also known as physical activation, involves using crushers and ball mills to break down coal gangue into micron-sized particles, increasing its specific surface area and thus its contact area with cement. Thermal activation removes impurities from the surface of coal gangue through high-temperature calcination, disrupting its original stable crystalline structure and generating a thermodynamically unstable glassy structure. Chemical activation involves introducing chemical reagents to react with the coal gangue and activate its reactivity; alkali activation is commonly used. Combined activation employs a combination of multiple activation methods to achieve a superior activation effect.

[0004] Coal has always held a vital position in my country's energy structure. However, the mining process faces numerous safety challenges: first, water hazards; second, the safety of the surrounding rock mass, leading to stress, rock fragmentation, and severe roadway damage; and third, the formation of goafs in coal mines causing ground subsidence and fissures. Therefore, grouting reinforcement technology is used to strengthen the surrounding rock of mines and tunnels, improving safety during coal mining. Summary of the Invention

[0005] This invention proposes a high-alumina coal gangue powder for the preparation of controllable inorganic grouting reinforcement materials for mining. Through specific activation methods and preparation techniques, high-alumina coal gangue powder can replace cement clinker to prepare inorganic grouting reinforcement materials for mining. The main objective is to improve the comprehensive utilization rate of high-alumina coal gangue, a coal-based solid waste, reduce the land occupation and environmental pollution caused by coal gangue accumulation, and simultaneously achieve the preparation of high-performance inorganic grouting reinforcement materials for mining.

[0006] The first aspect of this invention provides a method for preparing coal gangue powder, comprising the following steps:

[0007] (S1) The coal gangue raw material is crushed to obtain crushed material;

[0008] (S2) The crushed material is calcined to obtain calcined material;

[0009] (S3) Grind the calcined material to obtain the coal gangue powder;

[0010] In step (1), the aluminum content in the coal gangue raw material is ≥30wt%, and the amorphous phase content is ≥50%;

[0011] In step (2), the calcination temperature is 600-900℃.

[0012] A second aspect of the present invention provides a coal gangue powder prepared according to the preparation method described above.

[0013] A third aspect of this invention provides a composition for an inorganic grouting reinforcement material used in mining. By weight, the composition comprises 2400-2550 parts of coal gangue powder, 450-600 parts of an activator, 950-1000 parts of water, and 3-5 parts of an additive; wherein...

[0014] The activator is selected from at least one of potassium silicate, sodium silicate, calcium oxide, and silicate cement;

[0015] Preferably, the additive is selected from at least one of water-reducing agents, plasticizing agents, water-retaining agents, and defoamers.

[0016] A fourth aspect of the present invention provides a method for preparing the above-described composition, comprising the following steps:

[0017] (M1) The coal gangue powder is uniformly mixed with the activator to obtain the first mixture;

[0018] (M2) The water, water-reducing agent, plasticizing agent, water-retaining agent and defoamer are mixed evenly to obtain a second mixture;

[0019] (M3) Mix the first mixture and the second mixture evenly to obtain the composition;

[0020] The weight ratio of the coal gangue powder, activator, water, water-reducing agent, plasticizing expander, water-retaining agent and defoamer is (2400-2550): (450-600): (950-1000): (2-4): (0.1-0.2): (0.05-0.1): (0.5-1.5).

[0021] The beneficial effects of this invention are as follows:

[0022] I. This invention uses coal gangue with high aluminum content, which has more amorphous phase components after calcination, activation and pulverization. When these amorphous phase components participate in the hydration reaction of the inorganic grouting reinforcement material composition, they can make the material have better compressive strength and flow properties.

[0023] Second, this invention uses high-alumina coal gangue, which is crushed, calcined, and ground to prepare coal gangue powder. This process is simple to operate and requires no additives or water, nor does it generate waste residue or waste liquid. Furthermore, this coal gangue powder possesses high activity, with an activity index greater than 100%. It can partially replace cement in the preparation of inorganic grouting reinforcement materials, reducing cement usage and lowering carbon dioxide emissions.

[0024] Third, this invention provides a composition for preparing inorganic grouting reinforcement materials for mines using highly active coal gangue powder. The preparation process is simple and does not generate waste liquid. Furthermore, the resulting composition has a high coal gangue powder content and also possesses excellent flowability, controllable setting time, and excellent compressive strength. Detailed Implementation

[0025] The technical solution and its effects of the present invention will be further described below with reference to specific embodiments / examples. The following embodiments / examples are only for illustrating the content of the present invention, and the invention is not limited to the following embodiments or examples. Simple modifications made to the present invention based on the concept of the present invention are all within the scope of protection claimed by the present invention.

[0026] The first aspect of this invention provides a method for preparing high-alumina coal gangue active powder, comprising the following steps:

[0027] (S1) The coal gangue raw material is crushed to obtain crushed material;

[0028] (S2) The crushed material is calcined to obtain calcined material;

[0029] (S3) Grind the calcined material to obtain the coal gangue powder.

[0030] In some embodiments, in step (S1), the aluminum content in the coal gangue raw material is ≥30%; and the amorphous phase content in the coal gangue raw material is ≥50% as determined by XRD.

[0031] Preferably, the aluminum content in the coal gangue raw material is 30-50 wt%, and the amorphous phase content is 50-65%.

[0032] Among them, the amorphous phase refers to the mineral phase composition of coal gangue as determined by XRD testing, which includes crystalline and amorphous phases. Specifically, the amorphous phase is an amorphous (free) component.

[0033] The inventors have discovered that coal gangue with high aluminum content has more amorphous phase components after calcination and activation. When these amorphous phase components participate in the hydration reaction of the inorganic grouting reinforcement material composition, they can improve the material's performance (e.g., compressive strength).

[0034] In step (S1) of this invention, the crushing can be a one-time crushing, a batch crushing, or screening out crushed material that meets the particle size requirement (e.g., particle size less than 0.6 mm) from the raw material. Considering that the crushing in step (S1) will crush all the coal gangue raw material to below 0.6 mm, or requires a long time, in some embodiments, the coal gangue raw material is first crushed to a particle size ≤ 3 mm, and then crushed material with a particle size less than 0.6 mm is screened out.

[0035] In some embodiments, the particle size D of the crushed material 90 It can be 0.4-0.6mm, such as 0.5mm.

[0036] In some embodiments, before the calcination is carried out in step (S2), the crushed material is evenly spread in the muffle furnace according to certain rules and methods so that the coal gangue is calcined more evenly and fully.

[0037] Furthermore, the thickness of the crushed material should be 10-20mm. Too thick a layer will result in insufficient calcination at the bottom, while too thin a layer will lead to incomplete utilization of the equipment space and insufficient calcination volume per cycle.

[0038] Furthermore, the calcination method may be as follows: heating the crushed material to 600-900℃ at a rate of 2-4℃ / min, then holding it at that temperature for 2-4 hours, and finally cooling it to ambient temperature.

[0039] The calcination process activates the coal gangue, transforming its crystalline mineral phase into an amorphous phase, which then participates in subsequent hydration reactions. During calcination, insufficient holding time results in incomplete calcination of the coal gangue, while excessive holding time wastes energy.

[0040] In some embodiments, in step (S3), the particle size of the coal gangue powder obtained after grinding is ≤40μm, for example, it can be D. 90=20-40μm, for example 30μm. The grinding method can be selected from at least one conventional method in the art, such as mechanical ball milling or vertical grinding. For example, a ball mill with a rotation speed of 200-600 rpm and a grinding time of 10-60 min can be used to grind the calcined material to a particle size ≤40μm. Studies have found that under high-temperature calcination, coal gangue powder partially melts and agglomerates, destroying active sites. Simultaneously, the increased particle size of the coal gangue powder also hinders the exposure of surface active sites. This invention, by grinding after calcination, facilitates the activation of more active sites, thus aiding in subsequent reactions.

[0041] A second aspect of the present invention provides a coal gangue powder prepared according to the preparation method described above.

[0042] In this invention, the coal gangue powder has excellent activity and can replace cement in the preparation of inorganic grouting reinforcement materials for mines. In some embodiments, the activity index of the coal gangue powder is 100-115%.

[0043] The coal gangue powder used in this invention has a small particle size and a large specific surface area, which makes it easier to prepare the hydration reaction of the inorganic grouting reinforcement material composition, and can produce a micro-aggregate filling effect, making the cementitious material structure more compact.

[0044] The third aspect of the present invention provides a composition of an inorganic grouting reinforcement material for mining, wherein, by weight, the composition comprises 2400-2550 parts of coal gangue powder, 450-600 parts of activator, 950-1000 parts of water, and 3-5 parts of additives.

[0045] In this invention, the coal gangue powder is obtained by the above preparation method, and the activator is selected from at least one of potassium silicate, sodium silicate, calcium oxide and silicate cement.

[0046] In this invention, the activator is selected from at least one of potassium silicate, sodium silicate, calcium oxide, and silicate cement;

[0047] In some embodiments, the admixture may be selected from at least one of water-reducing agents, plasticizing agents, water-retaining agents, and defoamers. Those skilled in the art can select appropriate admixtures according to the actual situation.

[0048] Preferably, the water-reducing agent is selected from at least one of polycarboxylic acid derivatives, sulfonate derivatives, aliphatic derivatives, and polyvinyl alcohol; and / or

[0049] Preferably, the plasticizing agent is selected from at least one of silicates, calcium sulfoaluminate, calcium oxide, and organic acids; and / or

[0050] Preferably, the water-retaining agent is selected from at least one of cellulose ethers, polyacrylamides, and basic acrylic resins; and / or

[0051] Preferably, the defoamer is selected from at least one of organosilicon-based, polyether-based, and polyether-modified silicone-based defoamers.

[0052] In some embodiments, the weight ratio of the water-reducing agent, plasticizing agent, water-retaining agent, and defoamer is (2-4):(0.1-0.2):(0.05-0.1):(0.5-1.5).

[0053] The composition of the present invention uses a high content of coal gangue powder, and also has good strength and flowability.

[0054] The compositions of this invention have a controllable setting time, allowing technicians sufficient time to perform the grouting reinforcement process, and also exhibit early strength, increasing grouting efficiency. In some embodiments, the setting time (final setting) of the composition is 4-6 hours.

[0055] The compositions of the present invention exhibit excellent flowability. In some embodiments, the outflow velocity of the composition is 14-22 s, and the 30-minute flowability of the composition is ≤28 s.

[0056] The compositions of the present invention have excellent strength. In some embodiments, the 7-day compressive strength of the composition is ≥35 MPa, and the 28-day compressive strength of the composition is ≥50 MPa.

[0057] A fourth aspect of the present invention provides a method for preparing the above-described composition, comprising the following steps:

[0058] (M1) The coal gangue powder is uniformly mixed with the activator to obtain the first mixture;

[0059] (M2) The water, water-reducing agent, plasticizing agent, water-retaining agent and defoamer are mixed evenly to obtain a second mixture;

[0060] (M3) The first mixture and the second mixture are mixed uniformly to obtain the composition; wherein

[0061] The weight ratio of the coal gangue powder, activator, water, water-reducing agent, plasticizing expander, water-retaining agent and defoamer is (2400-2550): (450-600): (950-1000): (2-4): (0.1-0.2): (0.05-0.1): (0.5-1.5).

[0062] The present invention is further illustrated below through specific embodiments and comparative examples. Unless otherwise stated, the reagents, raw materials, and equipment used in the following embodiments and comparative examples are all commercially available in the art; wherein,

[0063] The coal gangue raw material comes from the Ordos region of Inner Mongolia.

[0064] The activator is ordinary Portland cement (Jidong Cement PO42.5), the water-reducing agent is Sika 530P, the plastic expansion agent is Dechang Weiye DC-C, the water-retaining agent is Dewey VM6310, and the defoamer is BASF F04.

[0065] The activity index was determined in accordance with the activity test content of high-activity powder in GB / T 1596—2017 "Fly Ash for Cement and Concrete".

[0066] The flowability at the outlet refers to the fluidity of the grout after it has been rolled out of the mixer under specific conditions; while the 30-minute flowability refers to the result of testing the flowability of the grout again after it has been mixed evenly in the mixer for 30 minutes. The test is conducted in accordance with GB / T 2419-2005 "Method for Determination of Flowability of Cement Mortar".

[0067] Setting time refers to the time required for cement or concrete to lose its plasticity after water is added. It is determined in accordance with GB / T1346-2011 "Standard Consistency Water Requirement, Setting Time and Soundness Test Methods for Cement".

[0068] The 7-day (or 28-day) compressive strength refers to the compressive strength value of concrete or grout after curing under standard curing conditions for 7 days (or 28 days), and is determined in accordance with GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete".

[0069] Examples 1-4 (IE1-4)

[0070] (1) The coal gangue raw material is mechanically crushed to less than 3mm in a jaw crusher, and then the crushed material with a particle size of less than 0.6mm (i.e., D) is screened out using a filter screen. 90 Approximately 0.5 mm); among which,

[0071] The coal gangue raw material has an aluminum content of 43 wt% and an amorphous phase content of 59%.

[0072] (2) The crushed material is calcined in a muffle furnace with a thickness of 15 mm. During the calcination process, the temperature is increased to the calcination temperature at a rate of 3 °C / min, then kept at the temperature for 3 h, and finally cooled to 25 °C at a rate of 4 °C / min.

[0073] The calcination temperatures were 550℃ (Example 1), 650℃ (Example 2), 750℃ (Example 3), and 850℃ (Example 4).

[0074] (3) The calcined material was mechanically ball-milled in a ball mill at a speed of 400 rpm for 30 min to obtain coal gangue powder with a particle size of less than 40 μm, i.e., particle size D. 90 =36.8μm.

[0075] Referring to GB / T 1596—2017 standard, the compressive strength of the mixture of coal gangue powder and cement (mixing ratio of 300:700) obtained in Examples 1-4 and pure cement were tested, and the activity index was calculated. The results are shown in Table 1 below. The activity index refers to the relative magnitude of the 28-day compressive strength of the coal gangue powder and pure cement mortar, with the activity index of pure cement mortar set at 100%.

[0076] Table 1:

[0077]

[0078] Table 1 shows that the activity index of coal gangue powder varies at different calcination temperatures. As the calcination temperature increases, the activity index first increases and then decreases, and the compressive strength of the resulting slurry also first increases and then decreases. Therefore, it can be inferred that when the calcination temperature is in the range of 600-900℃, the activity index of coal gangue powder is greater than 100%, and it can replace cement in the preparation of inorganic grouting reinforcement materials for mining.

[0079] Example 4 (IE4)

[0080] (1) The coal gangue is mechanically crushed to less than 3mm in a jaw crusher, and then screened with a filter to remove particles with a diameter of less than 0.6mm (i.e., D). 90 Crushed material (approximately 0.5mm); among which,

[0081] The coal gangue raw material has an aluminum content of 43 wt% and an amorphous phase content of 59%.

[0082] (2) The crushed material is calcined in a muffle furnace with a thickness of 15 mm. During the calcination process, the temperature is increased to 750°C at a rate of 3°C / min, then held for 3 hours, and finally cooled to 25°C at a rate of 4°C / min.

[0083] (3) The calcined material was mechanically ball-milled in a ball mill at a speed of 400 rpm for 30 min to obtain coal gangue powder with a particle size of less than 40 μm (particle size D). 90 =36.8μm).

[0084] (4) The coal gangue powder and the activator are mixed evenly in a stirring container to obtain a first mixture;

[0085] in,

[0086] The mass of the coal gangue powder is 2550g;

[0087] The activator has a mass of 450g.

[0088] (5) Mix 1000g water, 3g water-reducing agent, 0.1g plastic expansion agent, 0.1g water-retaining agent and 1g defoamer evenly to obtain the second mixture.

[0089] (6) Add the second mixture to the first mixture and stir continuously for 5 minutes until a uniform slurry is formed.

[0090] Example 5-7 (IE5-7)

[0091] Refer to Example 4, except that:

[0092] In step (4), the masses of the coal gangue powder and the activator are 2500g and 500g (Example 5, IE5), 2450g and 550g (Example 6), and 2400g and 600g (Example 7), respectively.

[0093] Examples 8-9 (IE8-9)

[0094] Refer to Example 4, except that:

[0095] In step (2), the coal gangue raw material with an aluminum content of 43 wt% and an amorphous phase content of 59% was replaced with coal gangue raw material with an aluminum content of 31 wt% and an amorphous phase content of 50% (Example 8) and coal gangue raw material with an aluminum content of 49 wt% and an amorphous phase content of 65% (Example 9).

[0096] Comparative Example 1-2 (CE1-2)

[0097] Refer to Example 4, except that:

[0098] In step (4), the masses of the coal gangue powder and the activator are 2000g and 1000g (Comparative Example 1), and 1000g and 2000g (Comparative Example 2), respectively.

[0099] Comparative Example 3 (CE3)

[0100] Refer to Example 4, except that:

[0101] In step (2), the coal gangue raw material with an aluminum content of 43 wt% and an amorphous phase content of 59% is replaced with a coal gangue raw material with an aluminum content of 16 wt% and an amorphous phase content of 37%.

[0102] Comparative Example 4 (CE4)

[0103] Refer to Example 4, except that:

[0104] Without performing step (3), the calcined material obtained in step (2) is directly screened, and the calcined material with a particle size of less than 0.6 mm is used as coal gangue powder.

[0105] The slurries obtained from Examples 4-7 and Comparative Examples 1-4 were tested for flowability at discharge, flowability at 30 min, setting time, compressive strength at 7 days, and compressive strength at 28 days. The test results are shown in Table 2 below.

[0106] Table 2:

[0107]

[0108] As can be seen from the comparison of Examples 4-9 and Comparative Examples 1-2 in Table 2, the total amount of coal gangue powder and activator is 3000g. With the increase of the amount of coal gangue powder, the fluidity (outflow fluidity and 30min fluidity refer to the time it takes to diffuse to the specified range, the longer the time, the worse the fluidity) and setting time of the grouting reinforcement material slurry decrease slightly, but the compressive strength increases. It can be used as a grouting reinforcement material.

[0109] As can be seen from the comparison of Examples 4, 8, and 9 and Comparative Example 3 in Table 2, compared with low-alumina coal gangue, the use of high-alumina coal gangue as the raw material for the active coal gangue powder in this invention significantly improves the compressive strength of the resulting grouting reinforcement material composition while maintaining relatively stable fluidity and setting time. Furthermore, the higher the aluminum content, the better the compressive strength.

[0110] As can be seen from the comparison between Example 4 and Comparative Example 4 in Table 2, grinding the calcined material of the present invention can make the coal gangue powder smaller in particle size and larger in specific surface area. When preparing the inorganic grouting reinforcement material composition, more active sites can be exposed, making the cementitious material structure more compact. The resulting inorganic grouting reinforcement material composition has better fluidity and higher compressive strength.

Claims

1. A method for preparing high-alumina coal gangue active powder, characterized in that, The preparation method includes the following steps: (S1) The coal gangue raw material is crushed to obtain crushed material; (S2) The crushed material is calcined to obtain calcined material; (S3) Grind the calcined material to obtain the coal gangue powder; In step (1), the aluminum content in the coal gangue raw material is ≥30wt%, and the amorphous phase content is ≥50%; In step (2), the calcination temperature is 600-900℃.

2. The preparation method according to claim 1, characterized in that, In step (1), The aluminum content in the coal gangue raw material is 30-50 wt%, and the amorphous phase content is 50-65%; and / or The particle size of the crushed material is less than 0.6 mm; Preferably, the particle size D of the crushed material is... 90 =0.4-0.6mm.

3. The preparation method according to claim 1 or 2, characterized in that, In step (2), The thickness of the shredded material is 10-20 mm; and / or The calcination heating rate is 2-4℃ / min, and the holding time is 2-4h.

4. The preparation method according to any one of claims 1 to 3, characterized in that, In step (3), The particle size of the coal gangue powder is less than 40 μm; Preferably, the particle size D of the coal gangue powder is... 90 =20-40μm.

5. A coal gangue powder prepared by any one of claims 1 to 4.

6. A composition of an inorganic grouting reinforcement material for mining, characterized in that, The composition, by weight, comprises 2400-2550 parts coal gangue powder, 450-600 parts activator, 950-1000 parts water, and 3-5 parts additives; wherein The coal gangue powder is the coal gangue powder prepared by the preparation method according to any one of claims 1 to 4, or the coal gangue powder according to claim 5. The activator is selected from at least one of potassium silicate, sodium silicate, calcium oxide, and silicate cement; Preferably, the additive is selected from at least one of water-reducing agents, plasticizing agents, water-retaining agents, and defoamers.

7. The composition according to claim 6, characterized in that, The water-reducing agent is selected from at least one of polycarboxylic acid derivatives, sulfonate derivatives, aliphatic derivatives, and polyvinyl alcohol; and / or The plastic expanding agent is selected from at least one of silicates, calcium sulfoaluminate, calcium oxide, and organic acids; and / or The water-retaining agent is selected from at least one of cellulose ethers, polyacrylamide, and basic acrylic resins; and / or The defoamer is selected from at least one of organosilicon, polyether, and polyether-modified silicone.

8. The composition according to claim 6 or 7, characterized in that, The weight ratio of the water-reducing agent, plasticizing agent, water-retaining agent, and defoamer is (2-4):(0.1-0.2):(0.05-0.1):(0.5-1.5).

9. The composition according to any one of claims 6 to 8, characterized in that, The setting time of the composition is 4-6 hours; and / or According to GB / T 50081—2019, the 7-day compressive strength of the composition is ≥35 MPa, and the 28-day compressive strength of the composition is ≥50 MPa; and / or According to GB / T 2419—2005, the outflow flowability of the composition is 14-22s, and the 30min flowability of the composition is ≤28s.

10. A method for preparing the composition according to claims 6 to 9, characterized in that, The method includes the following steps: (M1) The coal gangue powder is uniformly mixed with the activator to obtain the first mixture; (M2) The water, water-reducing agent, plasticizing agent, water-retaining agent and defoamer are mixed evenly to obtain a second mixture; (M3) Mix the first mixture and the second mixture evenly to obtain the composition; The weight ratio of the coal gangue powder, activator, water, water-reducing agent, plasticizing expander, water-retaining agent and defoamer is (2400-2550): (450-600): (950-1000): (2-4): (0.1-0.2): (0.05-0.1): (0.5-1.5).